Substanca milenijske dramske pisave v našem prostoru - Zajc, Benjamin (Amfiteater (Ljubljana), 2022)
n Slovenia, Croatia and Serbia, 21 st -century playwriting is strongly marked by the arrival of the millennial generation. If the older generation of playwrights was preoccupied with the memory of wars, questioning of collective guilt and condemnation of past political entities, and if the established contemporary dramatic corpus is expanded by questions of lost identity, feminism and critique of society, the millennial generation further complicates its dramatic construction with apprehension about globalisation and cultural erasure. As argues Stephan Dark, this gives their work a neo-miserabilist character. In millennial playwriting, which is less burdened by the events of the last century and more marked by the recent economic crises, we can observe even less optimism and utopian imagery. Instead, nihilism and cynicism prevail. Their material is self-referential and creates a world that corresponds to their own present. There is a particular focus on the individual’s attitude towards survival in an oppressive, corrupt and dysfunctional system, the individual’s search for meaning, related feelings of alienation and the inability to communicate. Through a selection of plays, this paper reflects on the key themes, the form and the atmosphere of millennial playwriting, which seems to be more marked by the uncertainty of the status quo than any previous generation.
Keywords: 21st-century drama; Dino Pešut; dramatic text; dramatika 21. stoletja; dramsko besedilo; Gorana Balančević; Iza Strehar; milenijska literatura; millennial literature